Application Effect and Prognosis of High-Quality Nursing in the Whole Process of Nursing in Lung Cancer Surgery. (17th August 2022) - Mei, Ling; Xu, Yan; Shi, Qingtong; Wu, Chen
Abstract : Objective . To explore the application effect and prognostic benefits of whole-course high-quality nursing in lung cancer patients after surgery. Methods . Sixty patients with lung cancer who underwent surgical treatment in the Department of Respiratory Medicine from April 2020 to July 2021 were recruited and assigned to receive either conventional nursing (control group) or whole-course high-quality nursing (intervention group) using the random number table method, with 30 cases in each group. Outcome measures included self-rating anxiety scale (SAS) scores, self-rating depression scale (SDS) scores, nursing compliance, patient satisfaction, complications, and patient prognosis. Results . Patients receiving whole-course high-quality nursing showed significantly lower SAS and SDS scores versus those given conventional nursing (P < 0.05 ). Whole-course high-quality nursing resulted in higher patient compliance versus conventional nursing (P < 0.05 ). Patients in the intervention group were more satisfied with the nursing compared with those in the control group (P < 0.05 ). Whole-course high-quality nursing resulted in a lower incidence of complications, postoperative recurrence, and mortality versus conventional nursing (P < 0.05 ). Conclusion . Whole-course high-quality nursing alleviates the negative emotions of patients after lung cancer surgery, enhances patient compliance and satisfaction, and reduces the incidence of postoperative relapse and complications, which demonstrates great potential for clinical promotion.